Retracted: Knowledge and practices of delivery room midwives on delayed umbilical cord clamping time: a descriptive study from Turkey - Deniz Akyildiz; Sena Dilek Aksoy (Faculty of Medicine, Universitas Andalas, 2023)
This article is retracted as requested by the authors. The previously published article is in volume 7, issue 2, 2022. The authors suspected that we do not exercise proper publication workflow and threaten us to report to all of our indexers if we do not fulfill the request. We are maintaining good relationship with everyone involves in our workflow, hence the retraction. To make everyone happy, the authors in this case. We are not a business entity. We are supporting the open access initiatives fully and try to maintain a proper publication process. The publication of the authors' articles are based on the authors' proposals. We never beg authors to submit their manuscripts. Those entirely based on authors request for publication.